Human Recombinant Alkaline Phosphatase (Ilofotase Alfa) Protects Against Kidney Ischemia-Reperfusion Injury in Mice and Rats Through Adenosine Receptors - Rosin, Diane L.; Hall, J. Perry; Zheng, Shuqiu; Huang, Liping; Campos-Bilderback, Silvia; Sandoval, Ruben; Bree, Andrea; Beaumont, Kevin; Miller, Emily; Larsen, Jennifer; Hariri, Ghazal; Kaila, Neelu; et al. (Frontiers in Medicine, 2022)
Adenosine triphosphate (ATP) released from injured or dying cells is a potent pro-inflammatory ‘danger’ signal. Alkaline phosphatase (AP), an endogenous enzyme that de-phosphorylates extracellular ATP, likely plays an anti-inflammatory role in immune responses. We hypothesized that ilofotase alfa, a human recombinant AP, protects kidneys from ischemia-reperfusion injury (IRI), a model of acute kidney injury (AKI), by metabolizing extracellular ATP to adenosine, which is known to activate adenosine receptors. Ilofotase alfa (iv) with or without ZM241,385 (sc), a selective adenosine A2A receptor (A2AR) antagonist, was administered 1 hr before bilateral ischemia-reperfusion injury (IRI) in WT, A2AR KO (Adora2a-/-) or CD73-/- mice. In additional studies recAP was given after IRI. In an AKI-on-CKD ischemic rat model, ilofotase alfa was given after the 3 instances of IRI and rats were followed for 56 days. Ilofotase alfa in a dose dependent manner decreased IRI in WT mice, an effect prevented by ZM241,385 and partially prevented in Adora2a-/- mice. Enzymatically inactive ilofotase alfa was not protective. Ilofotase alfa rescued CD73-/- mice, which lack a 5’-ectonucleotidase that dephosphorylates AMP to adenosine; ZM241,385 inhibited that protection. In both rats and mice ilofotase alfa ameliorated IRI when administered after injury, thus providing relevance for therapeutic dosing of ilofotase alfa following established AKI. In an AKI-on-CKD ischemic rat model, ilofotase alfa given after the 3rd instance of IRI reduced injury. These results suggest that ilofotase alfa promotes production of adenosine from liberated ATP in injured kidney tissue, thereby amplifying endogenous mechanisms that can reverse tissue injury, in part through A2AR-and non-A2AR-dependent signaling pathways.